2017
DOI: 10.3390/life7020026
|View full text |Cite
|
Sign up to set email alerts
|

DNA Protection Protein, a Novel Mechanism of Radiation Tolerance: Lessons from Tardigrades

Abstract: Genomic DNA stores all genetic information and is indispensable for maintenance of normal cellular activity and propagation. Radiation causes severe DNA lesions, including double-strand breaks, and leads to genome instability and even lethality. Regardless of the toxicity of radiation, some organisms exhibit extraordinary tolerance against radiation. These organisms are supposed to possess special mechanisms to mitigate radiation-induced DNA damages. Extensive study using radiotolerant bacteria suggested that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
81
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 63 publications
(73 reference statements)
6
81
0
Order By: Relevance
“…The possible explanation for the non-relativeness between an isolates' antibiotics resistance and its X-ray irradiation resistance can be attributed to their mode of attack. Antibiotics are tailored to be target specific on sites/organelles of organism or group of organisms while clinical X-ray radiations are not but result to oxidative stress [9,32].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The possible explanation for the non-relativeness between an isolates' antibiotics resistance and its X-ray irradiation resistance can be attributed to their mode of attack. Antibiotics are tailored to be target specific on sites/organelles of organism or group of organisms while clinical X-ray radiations are not but result to oxidative stress [9,32].…”
Section: Resultsmentioning
confidence: 99%
“…This is because clinical xrays which are designated human-tolerable are engineered to attenuate the adverse biological effects of their radiation on living cells [4,33]. Secondly, prokaryotes are known to exhibit much higher radiation tolerance than animals and humans [9]. As a result, the genotype profile of the cells may have been preserved using some form of reversion mechanism (such as base and nucleotide excision repair) [10,12] or defense mechanisms (catalase and superoxide dismutase synthesis) [13] thereby protecting the cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent in vitro study also confirmed that Dsup can protect chromatin DNA from hydroxyl radicals [252]. Currently, a Dsup homolog has only been found in another tardigrade species, Hypsibius exemplaris, which belongs to the same taxonomic family of R. varieornatus [252][253][254]. These findings indicate that tardigrades have evolved their own stress-resistant machinery in their lineages and such unique machinery can also function in human cells.…”
Section: Radioresistant Organismsmentioning
confidence: 88%